(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
This study aims to develop a scientific and methodological model for enhancing decision-making skills of law students through cognitive teaching methods. The research was conducted using a quasi-experimental design involving 59 participants. Traditional lecture-based instruction was applied in the control group, while the experimental group was taught using case-based learning, decision tree modeling, mind mapping, debate technology, and the integration of an AI-based legal chatbot. Decision-making skills were assessed according to four criteria: problem identification, generation of alternatives, normative justification, and logical conclusion formulation. The results demonstrated a statistically significant improvement in the experimental group (p < 0.05). The findings confirm the effectiveness of cognitive approaches in developing analytical thinking and professional decision-making competencies in legal education.